Posterior reversible encephalopathy syndrome induced by nivolumab immunotherapy for non–small‐cell lung cancer - Kim, Dohhyung (Clin Case Rep, 2019)
Posterior reversible encephalopathy syndrome (PRES) is a neurological syndrome characterized by vasogenic cerebral edema with predominantly posterior involvement. Uncontrolled severe hypertension and endothelial dysfunction have been implicated as two main mechanisms. Clinicians should notice the development of PRES in hypertensive patients accompanying neurological changes, such as impaired vision and consciousness.